FAR FROM THE BIG CITY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The cheese factories around Nakuru and the fruit processing plants close to Thika and Kitale in Kenya have found economic conditions in these production areas far more favourable than in Nairobi, especially when it comes to labour costs. In Uganda...